A REVISION OF BOEA (GESNERIACEAE) - Puglisi, C.; Middleton, D. J. (Edinburgh Journal of Botany, 2017)
The genus Boea Comm. ex Lam. is revised. Eleven species are recognised, including the new species Boea morobensis C.Puglisi. A key is provided, all names are typified, and the species are described.
Keywords: Australia; Loxocarpinae; Papua New Guinea; Solomon Islands; taxonomy; Waigeo